Techno-economic analysis of furfural/furfuryl alcohol derivatives at Sezela Sugar Mill - Kabwe, Taonga (Stellenbosch : Stellenbosch University, 2025)
Kabwe, T. 2025. Techno-economic analysis of furfural/furfuryl alcohol derivatives at Sezela sugar mill. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/942a4bd3-ed57-4e2e-9d9b-7e7c0295feb8